2021
DOI: 10.1128/msystems.00002-21
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally Validated Reconstruction and Analysis of a Genome-Scale Metabolic Model of an Anaerobic Neocallimastigomycota Fungus

Abstract: Anaerobic gut fungi in the phylum Neocallimastigomycota typically inhabit the digestive tracts of large mammalian herbivores, where they play an integral role in the decomposition of raw lignocellulose into its constitutive sugar monomers. However, quantitative tools to study their physiology are lacking, partially due to their complex and unresolved metabolism that includes the largely uncharacterized fungal hydrogenosome. Modern omics approaches combined with metabolic modeling can be used to establish an un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 77 publications
(145 reference statements)
3
63
0
1
Order By: Relevance
“…70,71 A list of genes associated with the fungal hydrogenosome of the C. churrovis strain was constructed based on homology with known hydrogenosome components, shown in Supplemental Table 3. FASTA sequences from known hydrogenosomal components identified in the fungal strain Neocallimastix lanati 4 were aligned to filtered model proteins of C. churrovis using the blastp alignment program in MycoCosm. One or more genes within the C. churrovis genome aligned to all listed hydrogenosomal enzymes found in N. lanati.…”
Section: Fungal Co-culture With a Methanogen May Enhance Pfl Function And Production Of Bottleneck Enzymes In Sugar Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…70,71 A list of genes associated with the fungal hydrogenosome of the C. churrovis strain was constructed based on homology with known hydrogenosome components, shown in Supplemental Table 3. FASTA sequences from known hydrogenosomal components identified in the fungal strain Neocallimastix lanati 4 were aligned to filtered model proteins of C. churrovis using the blastp alignment program in MycoCosm. One or more genes within the C. churrovis genome aligned to all listed hydrogenosomal enzymes found in N. lanati.…”
Section: Fungal Co-culture With a Methanogen May Enhance Pfl Function And Production Of Bottleneck Enzymes In Sugar Pathwaysmentioning
confidence: 99%
“…As shown in Supplemental Table 3, 21 genes were homologous to both pyruvate formate lyases (PFLs) that were identified in the N. lanati genome. 4 This enzyme reversibly converts pyruvate and CoA into acetyl-CoA and formate, which plays a central role in anaerobic glucose fermentation. 72 It has been shown that this enzyme is functional in hydrogenosomes of the anaerobic fungal species Piromyces sp.…”
Section: Fungal Co-culture With a Methanogen May Enhance Pfl Function And Production Of Bottleneck Enzymes In Sugar Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Such models have the potential to ‘predict phenotype from genotype’ [13] and hence to ‘transform bioscience and medicine’ [4]. Critical to understanding the large-scale metabolism within cells is the stoichiometric approach [5–8], which has had notable successes including the genome-scale reconstruction of the metabolism of Escherichia coli [911] and Neocallimastigomycota fungus [12].…”
Section: Introductionmentioning
confidence: 99%
“…Anaerobic fungi gain energy through mixed acid fermentation, with acetate, formate, succinate, lactate, ethanol, and hydrogen being the main products [ 32 , 33 ]. Production of hydrogen, acetate, and formate occurs mainly in the hydrogenosomes, organelles which have evolved from mitochondria lacking in AF [ 34 ].…”
Section: Introductionmentioning
confidence: 99%